STRATEGI PEMBELAJARAN KITAB KUNING (ANALISIS NILAI-NILAI AHLAK KARIMAH) DALAM KITAB WASOYA DI PONDOK PESANTREN MUSTHAFAWIYAH - Yona Riska Amelia Pasaribu; Zainal Efendi Hasibuan (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2025)
This study explores the learning strategies of classical Islamic texts (kitab kuning) and analyzes the moral values (akhlak karimah) found in the Wasoya book at Pondok Pesantren Musthafawiyah. The main problems addressed in this research are the strategies applied in the teaching of kitab kuning and how the moral values contained in Wasoya are integrated into the learning process. The kitab kuning serves as a primary source in traditional Islamic education, aiming not only to convey religious knowledge but also to instill ethical and spiritual values. This research employs a qualitative approach with field study and content analysis methods. Data were collected through observation, in-depth interviews with teachers and students, and documentation of teaching activities and the Wasoya text. The findings reveal that learning strategies such as bandongan, sorogan, and guided discussions are used, complemented by the habituation of moral behavior in daily life. The Wasoya book emphasizes values such as honesty, trustworthiness, humility, and compassion, which are instilled through both instruction and exemplary conduct by teachers. In conclusion, Pondok Pesantren Musthafawiyah effectively integrates classical text-based learning with character building grounded in Islamic moral values.